Muslim Insurgencies in Southeast Asia: Intractability, the Security Dilemma, and "Islamic Factor" - Ahmad-Norma Permata (Studia Islamika, 2006)
Three main points will be elaborated on in the following discussion. Firstly, the author would like to explain the chronology of the conflicts and at the same time reveal their intractable nature. Secondly, the author will analyze the cause of the conflict in terms of the security dilemma: whether the conflicts were triggered by real or assumed causes? Thirdly, the author will address the specific "Islamic" factor of the conflicts, which was denied by Southeast Asian governments as being among the features of the conflicts, and propose a more appropriate approach to it in order to reduce the intractability of the conflicts.DOI: 10.15408/sdi.v13i2.567